Valorization of natural fibres from African Baobab wastes by the production of activated carbons for adsorption of Diuron. - Nabais, Joao (2017)
In this work the potential of natural fibrous materials from African Baobab wastes for the production of activated carbons (ACs) has been evaluated. The wastes tested as precursors for the production of ACs were the bark, wood and seed from the Baobab tree. The activated samples present good structural and chemical characteristics. These features allowed us to test some of the most representative samples in the adsorption of Diuron pesticide from liquidphase.